PREVALENSI KOKSIDIOSIS PADA PEDET DI KABUPATEN KLATEN, JAWA TENGAH - , ZUNAIZAH QUDWATUNNISA, Prof.em.drh. Setyawan Budiharta, MPH.,Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Coccidiosis in calves causes a great loss in cattle industry. The disease has never been reported in Klaten, Central Java. The objectives of this current study was to reveal the prevalence of the disease and factors associated with the occurrence of the disease. A total of 191 fecal samples can experimented from calves was selected and used throughout the study. The samples were selected in a proportional multistage sampling strategy, i.e. from six subdistricts and nine villages. Calves whose fecal samples experimented with float method to showed the existence of oocyst were considered as suffering coccidiosis. Analysis data used chi-square computation to found out the associated among coccidiosis and variable, odds ratio and risk ratio used to found out the strength of them. Computation used the SPSS 16.0 programs which in 2007. The results reveal a coccidiosis prevalence of 41,4% among calves in Klaten. Sufficient sunlight and forage from outside the village are factors associated with the disease. Factors not associated from calves were age, breed, sex, origin, colostrums consumption, fecal consistency, anthelmentika and vitamin. Management variable not associated were type of barn, barn condition, the daily rearing, barn floor, fecal collection facilities, feeding, feed and water facilities, time of harvest forage, and fecal processing. Environmental variable not associated were source of water, elevation of location and barn position.